The beginning of culturally renaissance in Arab Gulf region in the first half from 20th century - مفيد كاصد الزيدي (College of Education for Women, 2019)
The present paper deal with the issue of the beginning of the culturally renaissance in emirates of Arab Gulf from 1914-1945 between tow world war has been attracting the attention of academic about the developments in many fields in the Arab Gulf at this time. The paper is divided into five sections. First section, deals with the geographic importance for the Arab Gulf region. Second section, the economic situations in the region before and after oil. The third section, talk for social situations, like population, tribe and tribes in society, and immigration. The fourth section, deals with the factors of rise the culture and political in the Arab Gulf before discovery of oil period. The five section, the culturally elements of modern education, library, culturally clubs and associations, press and papers.